Pemanfaatan Media Sederhana dalam Pembelajaran Fisika untuk Materi Udara bagi Kelompok Anak di Sentani - Radjabaycolle, Flinn C.; Bunga, Martina; Susilowati, Rachmadani O. (JURNAL PENGABDIAN PAPUA, 2025)
Physics is often perceived as one of the most difficult subjects, leading to a lack of interest, particularly among students. This issue is exacerbated by the reliance on rote memorization of formulas and definitions, rather than a deep understanding of the concepts. Such an approach hinders students' ability to think critically and creatively, which is essential for problem-solving in real-world applications. This community service program aimed to address these challenges by providing primary school children in Sentani, Jayapura, with engaging, hands-on experiments to better understand basic physical concepts, specifically the properties of air. The activities included simple experiments such as "Jar and Handkerchief", "Straw in a Glass", and "Paper Helicopter," which illustrated concepts like air occupying space, the behavior of liquids in a straw, and the effects of air on objects. The program aimed to create an interactive and enjoyable learning environment, where children could explore physics without the pressure of memorization. The results showed significant improvements in the children's engagement and understanding, with most participants expressing interest in continuing to learn physics. The study concludes that such interactive, experimental learning methods are effective in enhancing students' interest in science and improving their critical thinking skills, and recommends expanding these activities to reach a wider audience in the future.